2012
DOI: 10.1155/2012/503821
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions and Adherence to Guidelines for the Management of Hypertension: A National, Multicentre, Prospective Study

Abstract: Background. The aim of the current study was to investigate physicians' perceptions and adherence to the European guidelines for the management of hypertension. Methods. This is a national, multicentre, prospective, observational study, conducted between November 2007 and June 2008, in Cyprus. Consecutive hypertensive patients have been recruited by a random sample of physicians. The physicians' recommendations for every single patient have been recorded and compared with the 2007 ESH/ESC guidelines. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
3
23
0
1
Order By: Relevance
“…Studies have also revealed that changes in lifestyle patterns through the adoption of health behaviors can effectively improve an individual’s health conditions or alleviate symptoms of chronic diseases. For example, reduced intake of sodium, regular exercise, no smoking, and limited drinking are all recommended methods for controlling chronic diseases [ 10 , 11 , 12 ]. Previous findings have indicated that changes in lifestyle patterns exhibited by healthy individuals or individuals who have chronic diseases can be grouped into clusters [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also revealed that changes in lifestyle patterns through the adoption of health behaviors can effectively improve an individual’s health conditions or alleviate symptoms of chronic diseases. For example, reduced intake of sodium, regular exercise, no smoking, and limited drinking are all recommended methods for controlling chronic diseases [ 10 , 11 , 12 ]. Previous findings have indicated that changes in lifestyle patterns exhibited by healthy individuals or individuals who have chronic diseases can be grouped into clusters [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy lifestyle behaviors are associated with poor health status; however, these behaviors are modifiable. Researchers have discussed that changes in lifestyle patterns or adoption of health behaviors may effectively improve the conditions of those with chronic diseases, such as hypertension and diabetes [ 10 , 11 , 12 ]. Therefore, positive changes in health behaviors by reducing the identified modifiable lifestyle risk factors could prevent specific chronic diseases and promote health, thereby confirming the importance of preventive medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Theodorou et al studied adherence to European guidelines for the management of hypertension and found that even though physicians were aware of the clinical guidelines and the majority of patients received appropriate treatment advice and lifestyle recommendations, more than one fourth of high-risk hypertensive patients remained untreated and 40 % of low-risk patients received inappropriate medications [38]. Another study showed poor adherence to guidelines in hypertensive patients with diabetes and left ventricular hypertrophy [39].…”
Section: Discussionmentioning
confidence: 99%
“…No deja de ser preocupante el número de pacientes que reciben este medicamento como parte de su terapia antihipertensiva, puesto que los someten a un riesgo documentado largo tiempo atrás y cuyas causas pueden estar relacionadas con una falta de actualización por parte de los clínicos responsables de su atención, carencia de programas de educación médica continua y por falta de adherencia a las guías de práctica clínica que desde hace muchos años no consideraban al verapamilo en esta presentación como terapia antihipertensiva 13,14 . Por otro lado, se pudieron identificar las variables que se asociaron con incremento del riesgo de conseguir el cambio de la terapia con VLC por otro antihipertensivo, y de aquellas que reducían dicha probabilidad.…”
Section: Discussionunclassified